Conceptual understanding of circle elements for visual impairment students: Optimization of sound and tactile features in circle box learning media - Rahmatin, Tsania; Al Jupri; Suhendra (IKIP Siliwangi, 2025)
This study explores the conceptual understanding of visually impaired students regarding circle elements using a learning tool called the Circle Box, which incorporates auditory and tactile features to help students identify circle elements and facilitate subsequent learning. A qualitative naturalistic approach was employed, involving five 8th-grade visually impaired students and two mathematics teachers at a special school in Cimahi. Data were collected through observations, interviews, and a test adapted from Adding It Up: Helping Children Learn Mathematics by the National Research Council. Data were analyzed through reduction, descriptive presentation, verification, and conclusion. The results show that most students successfully identified circle elements and understood key relationships, though challenges remain in verbal explanations and generalizations involving unfamiliar vocabulary. Factors such as age, gender, and the level of visual impairment influence understanding, impacting memorization and confidence. Recommendations for improvements emphasize sound quality, simplified language, and enhanced tactile designs for better usability and learning efficiency.